Sputum Bacteriology and Antibiotic Sensitivity Pattern of Hospitalized Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease in Kathmandu Model Hospital - Dahal, Abhinav; Joshi, Rajesh Dhoj; Palikhe, Muna; Maskey, Neelima; Sah, Shyam Sundar; Onta, Aastha; Shrestha, Basudha (Journal of Nepal Health Research Council, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is the fourth leading cause of death in the world and will become the third leading cause of death worldwide by 2020. A study was carried out with an objective to study the sputum bacteriology and antibiotic sensitivity pattern of hospitalized patients with acute exacerbation of chronic obstructive pulmonary disease.Methods: A review study was carried out for a sputum culture isolated cases of acute exacerbation of COPD in Kathmandu Model Hospital. The discharged records from Jan 1st 2018 to December 31st, 2022. were analysed for demographic data and antibiotic susceptibility patterns. Any patient records with incomplete information were excluded from this study. An antibiotic susceptibility pattern was further confirmed from the laboratory records. Data were entered and analysed using SPSS version 21.Results: Over the period of five years from Jan 1st 2018 to December 31st, 2022. We found that total 80  of our patients with acute exacerbation of chronic obstructive pulmonary disease had a positive routine sputum culture. Pseudomonas aeruginosa (28.7%), Kleibsella pneumonia (20%), Escherchia coli (17.6%), Acinetobacter baumani complex (13.8%) were the most common bacteria isolated. Most organisms are found to be sensitive to Polymyxin B, Colistin, Tigecycline followed by Piperacillin/Tazobactam while most of them are found to be resistant to Amoxicillin, Amoxicillin/Clavulanic Acid and Cefixime. Conclusions: Pseudomonas aeruginosa, Klebsiella pneumonia and Escherchia coli accounted for most common bacteria isolated in our study. These bacteria were found to be sensitive to polymyxin B, colistin and tigecycline. Most of them were resistant to amoxicillin, amoxicillin clavulanic acid and cefixime. Our study concluded acute exacerbation of chronic obstructive pulmonary disease is associated with bacterial isolates in sputum culture and highly sensitive to broad spectrum antibiotics Keywords: Bacteria, COPD, exacerbation, sputum culture, antibiotics, Nepal